Program Qur’anic Teenagers untuk Menumbuhkan Minat Belajar Al-Qur’an bagi Anak dan Remaja di Desa Wakanimboro, Buton Selatan - Khaerul Aqbar; Askar Patahuddin (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
PkM aims to: (1) Foster social awareness of students in preaching based on Islamic science that has been obtained while in STIBA Makassar; (2) Practicing Tri Dharma of higher education for Field Guidance Lecturers (DPL) on the pillars of community service; (3) Develop the existence of STIBA Makassar as a university based on the recruitment of scholars and organizers who benefit the community. Therefore, PKM is held in the highland area of Wakinamboro Village, is one of 9 villages located in Siompu Subdistrict, South Buton Regency, Southeast Sulawesi Province. PkM is started by conducting a field survey and then continued by using SOAR analysis as a material to develop a work program, so that 2 activities for less touched areas da'wah because of its geographical location. The two activities are teaching the Qur'an and tahfiz class for teenager. The result of this activity is the ability to read and memorize the Qur'an children and adolescents in Wakinamboro Village increased. The community also felt very helped and thanked by the program held by students kkn STIBA Makassar because their children are able to read the Qur'an faster than ever.